新加坡华语韵母[-əŋ]变[-ən]的发音变化及其社会意义 = The sound change from [-əŋ] to [-ən] in Chinese as a socio-linguisitc indicator in Singapore - 张贻胜 Teo, Yi Sheng (2013)
在普通话音节中，鼻韵尾可分为［－n］韵尾和［－ŋ］韵尾两类。陈重瑜于1986年对新加坡华语的实地语音调查显示，［－əŋ］韵母出现念为［－ən］的语音现象。 本文通过100位介于17岁至70岁的被试（新加坡华语用语者）的语音采样，旨在确认陈重瑜的发现在相隔26年后是否依然存在。本文调查借用PRAAT语音软件，依据被试发鼻韵尾所呈现的语图在1400赫兹至2000赫兹之间是否存有共振峰条纹来辨别［－ŋ］和［－n］韵尾，并从中计算个别被试的［－əŋ］韵母音变百分比。之后利用Meade的语音变异标准将被试的音变百分比细分为“不存在”、“少数”、“不稳定”、“稳定”、“多数”和“完整”6种音变程度，并加上问卷调查的发现一起探究其中的音变原因。最后再计算职业、教育程度、年龄、方言、语体和性别共6种社会变量对［－əŋ］韵母念为［－ən］这种音变现象所产生的影响，希望从中探讨新加坡的语音教学，并且掌握这种音变的现状及未来趋势。In Standard Chinese syllable(普通话音节), a nasal coda exists either in the form of dental nasal [-n] or velar nasal [-ŋ]. An empirical study conducted by Chen Chung Yu on Singapore Chinese pronunciation by Singaporeans in 1986 showed a sound change phenomenon of pronouncing the final syllable [-əŋ] to [-ən]. Based on the sampling of the oral production recorded from a group of 100 Singaporean Chinese participants ranging from age 17 to age 70, this research aims to observe whether Chen Chung Yu’s finding remains valid after this period of 26 years. With the help of the PRAAT phonetic software, the two types of nasal codas is identified based on the presence of formants in the spectrogram within the frequency range of 1400Hz to 2000Hz when pronouncing the nasal coda, and thereafter this method is used to calculate the percentage of the sound change from [-əŋ] to [-ən] for each participant. Based on Meade’s “Category of Sound Change”, the percentage of the sound change of the participants is classified into 6 different degrees of sound change which are namely “absent”, “sporadic”, “inconsistent”, “consistent, “regular” and “full”. These different degrees of sound change, together with the data collected via recording of answers to the questionnaire by the participants, are used to discuss the possible reasons for the occurrence of this sound change. The contributing factors for the 6 different degrees of sound change are then examined with reference to sociolinguistic variables such as occupation, education level, age, dialect, contextual style and gender. The social significance of such differences are discussed, while also reviewing the teaching of Chinese pronunciation in Singapore and the future tendency of this sound change.